2024
DOI: 10.1039/d3dt02932h
|View full text |Cite
|
Sign up to set email alerts
|

Flexible NHC-aryloxido aluminum complex and its zwitterionic imidazolium aluminate precursor in ring-opening polymerization of ε-caprolactone

Santu Goswami,
Pranay Mandal,
Subham Sarkar
et al.

Abstract: Anionic donor-functionalized NHC (N-heterocyclic carbene) complexes of Al are rare. We report one such case here, a NHC-aryloxido AlMe2 complex [Al(L)Me2] (2), following a stepwise synthesis from the proligand [HO-4,6-tBu2-C6H2-2-CH2{CH(NCH=CHNAr)}]Br...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 104 publications
0
3
0
Order By: Relevance
“…3d metals like Mn, Fe, Co, and Ni have also come up as earth-abundant alternatives in recent times with impressive catalytic activity and functional group tolerance under mild conditions . Our recent interest lies in donor-tethered NHCs and CAACs (cyclic(alkyl)(amino)carbenes) with a flexible methylene linker between the carbene N-heterocycle and the donor moiety . In one of the recent works, cationic Rh (I) complexes based on a picolyl-tethered CAAC and its isomeric aziridine were found to be highly active and selective in olefin hydrosilylation catalysis ( A , B ; Chart ).…”
Section: Introductionmentioning
confidence: 99%
“…3d metals like Mn, Fe, Co, and Ni have also come up as earth-abundant alternatives in recent times with impressive catalytic activity and functional group tolerance under mild conditions . Our recent interest lies in donor-tethered NHCs and CAACs (cyclic(alkyl)(amino)carbenes) with a flexible methylene linker between the carbene N-heterocycle and the donor moiety . In one of the recent works, cationic Rh (I) complexes based on a picolyl-tethered CAAC and its isomeric aziridine were found to be highly active and selective in olefin hydrosilylation catalysis ( A , B ; Chart ).…”
Section: Introductionmentioning
confidence: 99%
“…6 Whereas AlMe 3 deprotonated only the phenolic-OH to give the zwitterionic B as an isolable intermediate, which is further deprotonated by KHMDS to give the AlMe 2 complex C (Figure 2). 7 Importantly, both A and C are stable toward the migration.…”
Section: ■ Introductionmentioning
confidence: 99%
“…24 In most cases, calcium is used as a catalyst for ring-opening polymerization. 25 Recently, Werner et al reported a calcium-based catalyst for the synthesis of bio-derived cyclic carbonate. 26 However, these catalysts are homogeneous, and heterogeneous calcium catalysts have not been reported to date.…”
Section: Introductionmentioning
confidence: 99%